“I stayed on the street, as if there was no COVID-19”: enacting practices of care with youth at risk of violence and social exclusion in Portugal - Ferreira, Patrícia (Frontiers in Sociology, 2024)
As the COVID-19 pandemic unfolded, a world of carelessness was made visible. Public health guidelines against the spread of COVID-19 (e.g., school closures, staying home, social distancing) have substantially affected youth’s health and well-being and highlighted the need for context-specific understandings of infection, risk, and care. Our research aims to contribute to a deeper understanding of the impacts of COVID-19 on boys and girls serving educational measures and placed in the custody of the juvenile justice system in Portugal during the pandemic. Sustained by the use of ethnographic principles and methods along with participatory techniques, this article uncovers complex entanglements between the public health measures to mitigate contagion and the dynamics that exacerbated socio-spatial dynamics of social exclusion and isolation, educational and (mental) health inequities, and lived and practiced forms of violence by youth-serving tutelary measures in Portugal’s six educational centers. Following Tronto’s feminist ethical–political proposal of care, I argue that COVID-19 became a lens to access youth care needs — self-care, care for others, care as essential work of nurturing affective trajectories and solidarities and promoting positive and non-violent relationships. By caring for youth stories, the engagement of researchers and professionals in this action-oriented research aimed to promote the enactment of practices of care with youth in the Portuguese detention centers as a way to positively affect their inhabited present, promote healthier lives and nurture the construction of caring and non-violent post-pandemic futures.